A study of association of diabetic foot ulcers and peripheral vascular disease - Khan, Yasmee; Khan, Manal M.; Jain, Aakansh; Namdev, Rohit K. (International Journal of Advances in Medicine, 2018)
Background: Diabetic foot ulcers (DFU) are a common, costly, complex, and disabling complication of diabetes resulting in lower-extremity amputations. Diabetes Mellitus (DM) is associated with an increase in the incidence of peripheral vascular disease (PVD) compared to non-diabetic subjects. DFU are divided into two types: neuropathic ulcers (NPU) and neuro-ischemic ulcers (NIU). PVD in association with neuropathy leads to neuro-ischemic ulcers (NIU). Methods: A cross-sectional observational study was conducted for eighteen months period from October 2016 to March 2018, on 120 type-2 DM patients presenting with DFU at tertiary centre in central India. Informed written consent, detailed history was obtained from the patients including duration of diabetes, history of hypertension, smoking, presenting symptoms and other complications related to diabetes. Examination of foot and evaluation for peripheral pulses, ankle brachial pressure index (ABI), neuropathy and blood pressure were done. Laboratory tests for HbA1C, lipid profile, blood urea, serum creatinine and urine albumin creatine ratio (urine ACR) were done. Statistical analysis used: t test, fisher exact test and univariate analysis. Results: In our study, 1594 patients with T2DM were studied, out of which 120 patients presented with new DFU. Mean age of the patients was 61.5years with an M: F ratio of 1.78:1. NIU was present in 36 and NPU in 84 out of 120 DFU patients. Neuro-ischemic ulcers (NIU) were more common among males (28/78 males vs 8/42 females). NIU was found to have significant association with smoking (25/36 patients), hypertension (28/38 patients) and longer duration of diabetes (13.1 vs 9.2years). Other diabetic complications, retinopathy (26/36 patients) and nephropathy (18/36 patients) were more prevalent in patients with NIU. Dyslipidemia was also found in 58.33% (21/36) patients with NIU however the association was insignificant. Conclusions: Diabetic foot ulcers are very debilitating complication of diabetes, and a leading cause of amputations all over the world. Because of increased association of peripheral vascular disease with diabetic foot ulcers there is a rise in prevalence of neuro-ischaemic ulcers. Early management of peripheral vascular disease is important to prevent development of neuro-ischaemic ulcers.